The Origin and Arrhythmogenic Potential of Fibroblasts in Cardiac Disease - Vasquez, Carolina (2012)
Fibroblasts play a major role in normal cardiac physiology and in the response of the heart to injury and disease. Cardiac electrophysiological research has primarily focused on the mechanisms of remodeling that accompany cardiac disease with an emphasis on myocyte electrophysiology. Recently, there has been increasing interest in the potential role of fibroblasts in cardiac electrophysiology. This review focuses on the arrhythmia mechanisms involving interactions between myocytes and fibroblasts. We also discuss the available evidence supporting the contribution of intracardiac and extracardiac sources to the fibroblast and myofibroblast populations in diseased hearts.